2020
DOI: 10.1007/s12055-020-01019-7
|View full text |Cite
|
Sign up to set email alerts
|

Flexible or rigid ring in mitral annuloplasty—do the results differ?

Abstract: Introduction Mitral valve annuloplasty has evolved over the decades since its introduction and Carpentier played a major role in developing the technique. Mitral valve repair is preferred over replacement for severe primary mitral regurgitation, as it restores normal life expectancy when successful and does not require lifelong anticoagulation. There is an ongoing debate regarding the choice of ring for mitral valve annuloplasty-rigid or flexible. At present, the choice of ring is based on the availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The study suggests that both rings are safe and effective in treating MV regurgitation with comparable and acceptable 5-year outcome, in keeping with the suggestions from previous studies [3]. One remarkable finding of this study is the reduction in LV size at 5 years in both groups with a trend favouring the flexible ring, although not significant [7], also in keeping with the outcome of the previously cited meta-analysis [4]. More than 30 years ago, Spence and colleagues [8] were already able to compare the effects of rigid and flexible rings in isolated porcine hearts, and found that fixation of the mitral annulus was disadvantageous to the systolic function of the left ventricle.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The study suggests that both rings are safe and effective in treating MV regurgitation with comparable and acceptable 5-year outcome, in keeping with the suggestions from previous studies [3]. One remarkable finding of this study is the reduction in LV size at 5 years in both groups with a trend favouring the flexible ring, although not significant [7], also in keeping with the outcome of the previously cited meta-analysis [4]. More than 30 years ago, Spence and colleagues [8] were already able to compare the effects of rigid and flexible rings in isolated porcine hearts, and found that fixation of the mitral annulus was disadvantageous to the systolic function of the left ventricle.…”
supporting
confidence: 88%
“…It must be emphasized that despite these findings and the available evidence from clinical and translational studies and guidelines, the selection of which ring to use is not regulated and is still typically dictated by surgeon's preference. In the latest issue of the Journal, the paper by Panicker and colleagues [7] provides a valuable and pragmatic contribution to the debate on the appropriateness of using flexible or rigid rings to treat degenerative MV regurgitation. In a retrospective analysis, the authors have followed up 112 young patients undergoing MV repair for primary degenerative MV regurgitation to ascertain the mid-term impact of flexible and rigid rings in terms of recurrent MV regurgitation and LV positive remodelling.…”
mentioning
confidence: 99%
“…It has been proved that the use of flexible rings is comparable to rigid rings in terms of mortality and regurgitation recurrence, 11,12 while the flexible band is more effective in preserving the MV area, probably by decreasing the parietal stress and respecting the physiological valve motility. 11,13,14 Accurate diagnosis of DMVD is essential for surgical planning: despite two-dimensional (2D) echocardiography leads the initial assessment of mitral anatomy and regurgitation (MR), specific softwares, that elaborate the three-dimensional (3D) transesophageal echocardiography (TEE) acquisitions, have been developed to assess more accurately the MV geometry and mobility 15,16 ; in particular, the 3D TTE evaluation appeared to be superior to the 2D TEE in providing measurements comparable to the surgical examination.…”
Section: 10mentioning
confidence: 99%
“…It has been proved that the use of flexible rings is comparable to rigid rings in terms of mortality and regurgitation recurrence, 11,12 while the flexible band is more effective in preserving the MV area, probably by decreasing the parietal stress and respecting the physiological valve motility 11,13,14 …”
Section: Introductionmentioning
confidence: 99%